Research progress on evaluation index of workers’ task performance - Zheyu HUANG; Yuhong SHEN; Jian ZHANG; Lihua HE; Yun WANG (环境与职业医学)
Task performance is an important concern in ergonomics. Task performance is often affected by adverse ergonomic factors, resulting in health and economic losses. How to utilize effective indicators to evaluate the degree of impact of adverse ergonomic factors on workers' task performance is particularly important. In this paper, we conducted a literature review and analysis on the impact of adverse ergonomic factors on workers' task performance, focusing on summarizing available physiological, psychological, and neurocognitive behavioral function test indicators for evaluating workers' task performance. This summary of existing evaluation indicators provided reference and guidance for future evaluations of the impact of adverse ergonomic factors on workers' task performance.